Female athlete's heart: Systolic and diastolic function related to circulatory dimensions. Issue 3 (20th May 2014) - Hedman, K.; Tamás, É.; Henriksson, J.; Bjarnegård, N.; Brudin, L.; Nylander, E.
<x xml:space="preserve">Abstract</x> There are relatively few studies on female athletes examining cardiac size and function and how these measures relate to maximal oxygen uptake (VO2max). When determining sports eligibility, it is important to know what physiological adaptations and characteristics may be expected in female athletes, taking body and cardiac size into account. The purposes of this study were (a) to compare right and left heart dimensions and function in female endurance athletes (ATH) and in non‐athletic female controls of similar age (CON); and (b) to explore how these measures related to VO2max. Forty‐six ATH and 48 CON underwent a maximal bicycle exercise test and an echocardiographic examination at rest, including standard and color tissue Doppler investigation. All heart dimensions indexed for body size were larger in ATH (all P < 0.01). The diastolic mitral E/A ratio was 27% higher in ATH (P < 0.001) while systolic left and right atrio‐ventricular longitudinal displacement was 7% (P = 0.002) and 15% (P < 0.001) larger in ATH, respectively. Half (50.3%) of the variability in VO2max could be explained by left ventricular end‐diastolic volume. Our results could be useful in evaluating female endurance athletes with suspected cardiac disease and contribute to understanding differences between female athletes and non‐athletes.